Membrane covering material for metal stent, preparation method of membrane covering material and corresponding membrane covering stent
Preparation of coating scaffolds by ultraviolet curing E-PLCL and other materials has solved the shortcomings in stability, flexibility and application breadth of existing coating scaffold materials, and achieved coating materials with high mechanical properties, biodegradability and drug loading functions.
Patent Information
- Application Number
- CN202411984053.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing coating stent materials have problems such as insufficient stability, poor flexibility, and prone to inflammation and thrombosis in long-term use, and electrospinning technology is difficult to evenly cover the surface of complex stents.
UV light curing bioabsorbable elastomer resin material is used to prepare a material suitable for coating scaffolding through the combination of E-PLCL, free radical inhibitor and photoinitiator, and a fully coated tissue engineering scaffolding is formed through photocuring technology.
The coating material with high mechanical properties, biodegradability, simple processing method, can complete the coating of various shapes of brackets, and has drug loading functions, solving the shortcomings of existing materials in terms of stability, flexibility and application breadth.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure HDA0005222164010000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new biomedical materials, and specifically discloses a coating material for a metal stent, a preparation method thereof, and a corresponding coating stent. Background Art
[0002] A covered stent is a medical device with a layer of polymer or biofilm attached to the surface of a bare metal stent. It is widely used in the treatment of aneurysms, vascular ruptures, and stenosis of blood vessels, esophagus, trachea, and intestines. Although traditional bare metal stents can provide mechanical support, they are prone to cause intimal hyperplasia, leading to restenosis. In order to overcome this defect, covered stents effectively isolate blood flow from the vascular intima by adding a layer of membrane material to the surface of the stent, reducing the risk of intimal hyperplasia. Existing covered stents usually use non-degradable polytetrafluoroethylene (PTFE), polyurethane or polyester as the covering material. These materials have good biocompatibility and mechanical properties. However, there are still several challenges with traditional non-degradable covering materials, mainly focusing on the long-term stability of the membrane material, the flexibility and compliance of the stent, and the risks of inflammation, hyperplasia, thrombosis, etc. caused by long-term placement.
[0003] At present, the demand for biodegradable coated stents is gradually increasing. Researchers have gradually developed biodegradable coated stents based on materials such as polylactic acid (PLA), polyglycolic acid (PGA), polycaprolactone (PCL), and poly(L-lactide-co-ε-caprolactone) (PLCL). These materials can gradually degrade after completing their therapeutic functions, reducing the complications caused by long-term implantation. However, due to the problems of high melting point, high viscosity, and high elastic modulus of the above materials, electrospinning technology is currently used for stent coating. Although electrospinning technology has certain advantages in the preparation of coated stents, its processing method and material properties also bring some problems that cannot be ignored: First, due to the relatively fragile fiber structure of the electrospinning layer, the coating layer is easily torn or detached due to mechanical stress during the installation and deployment of the stent, which greatly affects the stability and efficacy of the stent. Secondly, it is difficult for electrospinning technology to evenly cover the surface of special-shaped stents, such as the coating of L-shaped and Y-shaped stents. This limitation not only affects the reliability of coated stents in clinical applications, but also limits their wide application in more complex lesions. Therefore, there is an urgent need for a coating material that has high mechanical properties, is biodegradable, has a simple processing method, can be used to coat stents of various shapes, and has drug loading function. Summary of the invention
[0004] In view of the problems and shortcomings in the prior art, the present invention aims to provide a UV-curable bioabsorbable elastomeric resin suitable for coated stents, and designs and prepares a fully coated tissue engineering scaffold based on the resin.
[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:
[0006] The first aspect of the present invention provides a coating material for a metal stent, which is composed of E-PLCL, a free radical inhibitor and a photoinitiator, wherein the addition amount of the free radical inhibitor is 0.05% to 0.5% of the weight of the E-PLCL, and the addition amount of the photoinitiator is 0.2% to 2% of the weight of the E-PLCL; the E-PLCL is prepared by double-bond modification of PLCL diol by allyl isocyanate.
[0007] The free radical inhibitor is 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical or 2,2,6,6-tetramethylpiperidin oxide; the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or 2,4,6-trimethylbenzoyl ethyl phosphonate.
[0008] The double bond modification method of the E-PLCL is as follows: PLCL diol is dissolved in toluene to form a solution with a concentration of 15wt% to 40wt%, and then allyl isocyanate is added, and the mixture is reacted at 50 to 80°C for 0.5 to 1.5h to obtain the obtained product; the molar ratio of the terminal hydroxyl group of the PLCL diol to allyl isocyanate is 1:(1.2 to 1.5).
[0009] The molecular weight of PLCL diol is 3000-10000;
[0010] The second aspect of the present invention provides a method for preparing the coating material for the metal stent according to the first aspect, comprising the following steps:
[0011] Step S1: preparing PLCL diol;
[0012] Step S2: dissolving PLCL diol in toluene to form a solution with a concentration of 15 wt% to 40 wt%, then adding allyl isocyanate, and reacting at 50 to 80° C. for 0.5 to 1.5 h to obtain E-PLCL;
[0013] Step S3: mixing the E-PLCL with the free radical inhibitor and the photoinitiator, and removing bubbles by ultrasound to obtain a bioabsorbable elastomer resin.
[0014] Step S1: The specific method for preparing PLCL diol is as follows: lactide, ε-caprolactone, diol, and stannous octoate are added into a reaction kettle, and stirred for reaction at 130-160° C. under vacuum and oxygen-free conditions for 8-16 hours to obtain poly(L-lactide-co-ε-caprolactone) diol, that is, PLCL diol;
[0015] The molar ratio of lactide, ε-caprolactone and diol is 0.165:0.658:(0.01-0.0125);
[0016] The diol is selected from one or more of 1,6-hexanediol, ethylene glycol or triethylene glycol.
[0017] The third aspect of the present invention provides a stent graft, comprising a metal stent and a coating layer, wherein the coating layer is formed by impregnating or coating the metal stent with the coating material for the metal stent according to claim 1 or 2, and then light-curing the coating material. The coating material prepared by the present invention is in a viscous liquid state at about 40°C and can be directly used for impregnation or coating.
[0018] The coated stent is also loaded with drugs, which are mixed into the coating material for the metal stent and loaded after being photocured together with the coating material.
[0019] A fourth aspect of the present invention provides a method for preparing the stent graft according to the third aspect, comprising the following steps:
[0020] (1) Immersing the metal stent in the metal stent coating material and ultrasonically treating at 40 to 50° C. for 25 to 35 minutes;
[0021] (2) taking out the metal stent treated in step (1), and subjecting it to vacuum heat treatment at 40 to 50° C. for 15 to 25 minutes;
[0022] (3) Curing the metal stent treated in step (2) under a 365-406 nm ultraviolet lamp for 10-15 min to obtain an E-PLCL fully coated stent.
[0023] The material of the metal bracket is nickel-titanium alloy or magnesium alloy.
[0024] The vacuum heat treatment is performed by suspending the sample in a vacuum oven.
[0025] The ultrasonic treatment in step (1) is to allow the E-PLCL to fully wrap around the surface of the metal stent and remove bubbles.
[0026] Step (2) vacuum heat treatment further removes bubbles.
[0027] The mechanical properties of coating materials, such as elastic modulus, elongation at break, and ultimate tensile strength, are critical for applications such as tracheal stent coatings. Low elastic modulus allows the stent to be easily compressed for placement and to flexibly expand after implantation to accommodate respiratory movements. High elongation at break and tensile strength enable the coating to withstand significant deformation without cracking or damage, ensuring structural integrity. In addition, high elasticity allows the coating to recover quickly under repeated stress. In summary, these properties ensure that the coated stent remains flexible, durable, and able to adapt to dynamic deformation under physiological conditions. Current photopolymerizable biomaterials mainly include softer gel formulations (0.1-100 kPa) and harder highly cross-linked resins (100 MPa), lacking elastomeric resins (low MPa, high elongation). Photocurable PLCL not only has the advantages of PLCL, such as good biocompatibility, non-toxic degradation products, biodegradability, and drug permeability, but also makes up for the slow degradation rate of poly(ε-caprolactone) (PCL). Further, for the photocurable functional modification of resin materials, acrylate functionalization is considered the gold standard. However, despite the rapid cross-linking kinetics of acrylates, the brittleness of the resulting materials limits their applicability and still makes it difficult to meet the requirements for stent graft materials. Although traditional polyurethane acrylate modification improves the mechanical properties of acrylate materials, its functionalization degree is low because the modification requires two steps. At the same time, there is usually low selectivity between the two isocyanate groups during the modification process, resulting in the formation of repeating units within the central backbone, which limits the improvement of mechanical properties.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention uses allyl isocyanate as a modifier, and the terminal hydroxyl groups of diols (or polyols) are reacted with allyl isocyanate to modify the double bonds of PLCL diol. The modification can be completed in only one step, and the degree of functionalization can reach more than 95%. The mechanical properties are higher than those of the polyurethane acrylate material modified by the traditional two-step method.
[0030] (2) The present invention synthesizes low molecular weight PLCL, and further modifies the obtained E-PLCL to successfully reduce the initial viscosity of PLCL while retaining the advantages of high molecular weight PLCL. The obtained photocurable material has low modulus and high elongation at break, good ductility and excellent fatigue resistance, which effectively solves the problem that the elastic modulus of biodegradable printing materials in the existing photocurable material library is too high and difficult to match with human tissue, filling the technical gap of photocurable biodegradable elastomer resin materials.
[0031] (3) The photocurable resin material of the present invention has the characteristics of low viscosity, low processing temperature, good biocompatibility, etc. It can be loaded with drugs and can also be mixed with cells for printing. The coating has a sustained release property after loading the drug. By combining drugs with different characteristics, the advantages of the stent in local drug treatment can be further exerted. The preparation method of the coated stent of the present invention is not limited by the shape of the stent, and the coating of the stent of any shape can be quickly achieved.
[0032] (4) By adjusting the molecular weight, ratio and cross-linked network structure of the material, the photocurable biodegradable elastomer material of the present invention has excellent versatility and is suitable for applications in the fields of tissue repair, nerve conduits, artificial blood vessels, tracheal stents, artificial cartilage and drug sustained-release systems. In addition to being suitable for stent coating, it can also be used in UV-curable 3D printers. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the preparation process of the light-cured biodegradable elastomer E-PLCL coated stent of the present invention;
[0034] Figure 2 The synthesis and modification routes of E-PLCL in Examples 1 to 4 and the results of nuclear magnetic resonance and infrared spectroscopy analysis are shown;
[0035] Figure 3 DSC curves of E-PLCL of Examples 1 to 4;
[0036] Figure 4 The results of the degradation experiment of E-PLCL fully covered stents in Examples 1 to 4 are shown;
[0037] Figure 5 The mechanical properties test diagram of E-PLCL of Examples 1 to 4;
[0038] Figure 6 The in vitro biocompatibility test results of Examples 1 to 4 are shown;
[0039] Figure 7 Viscosity test graphs of E-PLCL of Examples 1 to 4;
[0040] Figure 8 The prepared E-PLCL stent graft and Y-shaped stent graft;
[0041] Fig. 9 The experimental diagrams of E-8000 spline cyclic tension and E-PLCL stent graft cyclic compression;
[0042] Fig.10 This is a diagram of the E-PLCL stent graft compression and passing through the implantation catheter in the present invention;
[0043] Fig.11This is a drug release experiment diagram of the E-PLCL / DOX drug-eluting coated stent in the present invention;
[0044] Fig.12 This is a graph showing the inhibition of KYSE150 human esophageal cancer cells by the E-PLCL / DOX drug-eluting coated stent of the present invention. DETAILED DESCRIPTION
[0045] It should be noted that the following detailed description is exemplary and is intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein shall have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs. For the experimental methods in the following examples where specific conditions are not specified, conventional techniques in the art or conditions recommended by the manufacturer are used; if the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased on the market.
[0046] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the present invention is now further described in detail through specific embodiments, but these embodiments should not be regarded as limiting the scope of the present invention.
[0047] (I) Effect of different molecular weights on material properties
[0048] Example 1
[0049] A coating material for a metal stent, the preparation method comprising the following steps:
[0050] Step S1: Synthesis of PLCL-10000
[0051] First, a Schlenk reaction bottle equipped with a magnetic stirrer was flame dried. Then, 75.10 g (0.658 mol) of ε-caprolactone, 23.71 g (0.165 mol) of lactide, 1.18 g (0.01 mol) of 1,6-hexanediol, and 0.5 g (1.234 mmol) of Sn(Oct)2 were added to the bottle. After that, nitrogen was purged for 30 minutes, and a vacuum machine was used to draw a vacuum for 30 minutes to form a vacuum oxygen-free state. Then, the reactants were stirred at 150 ° C for 16 hours to obtain the final product PLCL-10000.
[0052] Step S2: Olefin functionalization of PLCL (E-PLCL synthesis)
[0053] 10 g of PLCL-10000 diol was dissolved in toluene to form a solution with a concentration of 15 wt%, and then allyl isocyanate (0.25 g, 0.003 mol) was added and reacted at 60° C. for 1 h. The final product E-10000 was obtained by precipitation in cold anhydrous ethanol.
[0054] Step S3: Preparation of light-curable PLCL materials
[0055] Taking 5 g of E-10000 as a quantitative basis, 0.1% of Tempol and 1% of TPO-L were added, mixed and stirred, and subjected to ultrasound for 30 minutes to remove bubbles, thereby obtaining a coating material for a metal stent.
[0056] A degradable tissue engineering covered scaffold, the preparation process is as follows Figure 1 As shown, the preparation method comprises the following steps:
[0057] (1) The nickel-titanium alloy stent was immersed in a liquid of a coating material for a metal stent and subjected to ultrasonic treatment at 45°C for 30 min to allow the E-PLCL to fully wrap around the surface of the nickel-titanium alloy stent and remove bubbles;
[0058] (2) Take out the nickel-titanium alloy stent treated in step (1), and place it in a vacuum oven at 45°C for 20 minutes to further remove bubbles. E-PLCL forms a thin film on the surface of the stent under the action of surface tension, and excess E-PLCL will drip;
[0059] (3) Curing the nickel-titanium alloy stent treated in step (2) under a 365-406 nm ultraviolet lamp for 15 minutes to obtain an E-PLCL fully coated stent.
[0060] The preparation of stent grafts is not limited by the shape of the stent, and stent grafting of any shape can be achieved quickly.
[0061] Example 2
[0062] Example 2 only completes steps S1, S2, and S3 in Example 1, and its content is basically the same as that of Example 1, except that:
[0063] In step S1, the amount of 1,6-hexanediol added is 3.94 g (0.033 mol), and the final product is PLCL-3000;
[0064] In step S2, the amount of allyl isocyanate added is 0.83 g, and the final product is E-3000.
[0065] Example 3
[0066] Example 3 only completes steps S1, S2, and S3 in Example 1, and its content is basically the same as that of Example 1, except that:
[0067] In step S1, the amount of 1,6-hexanediol added was 1.97 g (0.0167 mol), and the final product was PLCL-6000;
[0068] In step S2, the amount of allyl isocyanate added is 0.42 g, and the final product is E-6000.
[0069] Example 4
[0070] Example 4 only completes steps S1, S2, and S3 in Example 1, and its content is basically the same as that of Example 1, except that:
[0071] In step S1, the amount of 1,6-hexanediol added is 1.48 g (0.0125 mol), the stoichiometric ratio of the initiator to the monomer is 1:66.69, and the final product is PLCL-8000;
[0072] In step S2, the amount of allyl isocyanate added is 0.31 g, and the final product is E-8000.
[0073] The E-PLCL prepared in Examples 1 to 4 was characterized and its performance tested:
[0074] (1) Characterization by H NMR and IR
[0075] The E-PLCL with different molecular weights in Examples 1 to 4 were subjected to nuclear magnetic resonance hydrogen spectrum and infrared spectrum analysis tests. The results are as follows: Figure 2 The results of H NMR showed that a peak at 5.8 ppm corresponded to the olefin protons of the introduced allyl group, indicating the rapid conversion of the terminal hydroxyl functional group ( Figure 2 b) In infrared spectroscopy, at 3500cm -1 (NH stretching of urethane groups), 1635 cm -1 (allyl C=C stretching) and 804 cm -1 The characteristic peak at (Ch bending vibration of allyl group) further proves the success of post-polymerization modification ( Figure 2 c).
[0076] (2) Thermal analysis characterization
[0077] Differential scanning calorimetry (DSC) tests were performed on the E-PLCLs of different molecular weights in Examples 1 to 4. The results are as follows: Figure 3 shown. Figure 3 Differential scanning calorimetry (DSC) analysis showed that the melting point of E-10000 was significantly higher than that of other samples, at around 37°C.
[0078] (3) Degradability test
[0079] In order to evaluate the degradation behavior of E-PLCL, the E-PLCL prepared in Examples 1 to 4 and the thermoplastic PLCL (300000 g / mol) were subjected to 0.05 M NaOH accelerated degradation test and PBS degradation test. The experimental results are shown in Figure 4 The experimental results show that E-PLCL has good degradability. In particular, as the molecular weight of E-PLCL increases, the degradation time is significantly prolonged, which indicates that the degradation time of the stent can be controlled by selecting E-PLCL with different molecular weights to meet the requirements of different stent coatings.
[0080] (4) Mechanical properties test
[0081] The mechanical properties of the coating material, such as elastic modulus, elongation at break, and ultimate tensile strength, are critical for stent coatings. Low elastic modulus allows the stent to be easily compressed for placement and flexibly expand after implantation to accommodate respiratory movements. High elongation at break and tensile strength allow the coating to withstand significant deformation without cracking or failure, ensuring structural integrity. In addition, high elasticity allows the coating to recover quickly under repeated stress.
[0082] The E-PLCL prepared in Examples 1 to 4 was subjected to tensile tests and elastic modulus tests. The results are as follows: Figure 5 As shown in Table 1, the mechanical properties of E-PLCL vary with the molecular weight of the precursor: elongation at break 588% to 1595%, ultimate tensile stress 2.67 to 14.86 MPa, and elastic modulus 0.96 MPa to 2.16 MPa. The higher the molecular weight of the E-PLCL precursor, the lower the Young's modulus, while the ultimate tensile strength and elongation at break increase. The increase in the Young's modulus of E-10000 can be attributed to its semi-crystalline nature. The results of thermal analysis show that the melting point of E-10000 is significantly higher than that of other samples. This semi-crystalline structure masks the expected contribution of the cross-linking density and becomes the main factor controlling the Young's modulus under tensile conditions.
[0083] Table 1 Mechanical properties of E-PLCL in Examples 1 to 4
[0084]
[0085] (5) Biocompatibility test
[0086] 1. Transwell cell co-culture
[0087] To verify the biocompatibility of E-PLCL, we co-cultured E-PLCL with L929 cells using a transwell system and performed live-dead staining and CCK-8 assays at 1, 3, and 7 days. Figure 6 a. Figure 6 b. Figure 6c) The results showed that there was no significant difference in cell growth between the E-PLCL groups with different molecular weights and the pure PLCL group. This indicates that E-PLCL exhibits good biocompatibility in a cell culture environment and does not significantly affect cell growth and reproduction regardless of changes in its molecular weight.
[0088] 2. Subcutaneous Implantation Experiment in Mice
[0089] The E-PLCL samples with different molecular weights were implanted subcutaneously in mice for 1 and 4 weeks ( Figure 6 d. Figure 6 e). Specifically, 6-8 week old Bcl-2 female mice were used, and an incision was made in the abdomen. The 3D printed 4×2×1mm implant was placed in the pocket and the incision was sutured. Three mice were operated on in each group, and two implants were implanted on each side. The control group underwent the same operation using high molecular weight PLCL. The behavior and body weight of the mice were observed during the study, and the mice were euthanized and autopsied at 1 week and 4 weeks after implantation. The implants were fixed together with the surrounding tissues for histopathological evaluation. The experimental results showed that when all components were implanted for one week, mild acute inflammation occurred around the implant tissue, and the inflammation subsided at 4 weeks, and no signs of host immune response were found. This further verified the biocompatibility of E-PLCL in vivo, indicating its safety and reliability in biomedical applications.
[0090] (6) Viscosity test
[0091] The viscosity of the E-PLCL prepared in Examples 1 to 4 was tested, and it can be seen that as the temperature increases, the viscosity of all components of E-PLCL decreases significantly ( Figure 7 Considering the uniformity of the coating during the dip coating process, E-8000 exhibits a good balance of low viscosity and mechanical properties at moderate temperatures (less than 50°C), making E-8000 the optimal choice as the stent coating material.
[0092] Referring to Example 1, the E-PLCL prepared in Example 4 was used to prepare a stent graft, and its performance was tested.
[0093] Figure 8 a(i) shows the effect of using E-8000 to coat the NiTi alloy bare stent before and after. Figure 8 a(i) The left one is a bare stent, and the middle one is an E-PLCL covered stent (E-8000). Figure 8 The SEM image of a(ii) shows that the prepared coated stent has a uniform coating and a smooth surface. In addition, the E-PLCL coating method was successfully applied to the preparation of coated Y-shaped stents, demonstrating its adaptability to stents with complex geometric shapes ( Figure 8b). After 1000 cycles of stretching to 500% strain, E-8000 can fully recover its shape, showing excellent elasticity and adaptability to the dynamic environment of the trachea ( Fig. 9 a). Cyclic compression test further verified the mechanical properties of E-PLCL stent graft ( Fig. 9 b). Compared with the NiTi alloy bare stent, the E-PLCL coated stent exhibited smaller hysteresis loops and less residual deformation, indicating greater fatigue resistance and energy absorption capacity. Over more than 1000 compression cycles, the E-PLCL coated stent maintained unchanged mechanical properties with minimal deformation recovery loss, as evidenced by the stable force-displacement curves. Fig.10 a and Fig.10 b, Visually demonstrates the ability of the E-PLCL stent graft to fully recover its original shape after cyclic compression. In addition, the E-PLCL stent graft can be easily compressed and successfully delivered through a delivery catheter, confirming its adaptability for implantation ( Fig.10 c). These findings highlight the effectiveness of E-PLCL coating in providing durability and flexibility, making it well suited for tracheal stent applications.
[0094] (II) Differences in the effects of modified PLCL diol on the mechanical properties of materials by one-step and traditional two-step methods
[0095] Examples 1 to 4 use the one-step method provided by the present invention to modify PLCL diol. Comparative Examples 1 to 4 are set below, in which PLCL diol is modified by the traditional two-step method, and the mechanical properties of the two groups of samples are observed to investigate the effects of different processes on the mechanical properties of the modified PLCL diol.
[0096] Comparative Example 1
[0097] Step S1 of Comparative Example 1 is the same as that of Example 1;
[0098] Step S2: Olefin functionalization of PLCL (PE-PLCL synthesis)
[0099] 10g of PLCL-10000 diol was dissolved in toluene to form a solution with a concentration of 15wt%, and then L-lysine ethyl diisocyanate (LDI, 0.9g, 0.004mol) was added, and stannous octoate was added at a comonomer molar ratio of 1%. The reaction was carried out at 40°C under a dry argon atmosphere for 6h. Subsequently, 2-hydroxyethyl acrylate (HEA, 0.46g, 0.004mol) was added dropwise to the reaction mixture and reacted at room temperature for 24h. The polymer was concentrated under reduced pressure and precipitated in cold anhydrous ethanol to obtain the final product PEUA-10000.
[0100] Comparative Example 2
[0101] Comparative Example 2 completes steps S1 and S2 in Comparative Example 1, and its contents are substantially the same as those in Comparative Example 1, except that:
[0102] In step S1, PLCL-3000 obtained in step S1 of Example 2 is used;
[0103] In step S2, the amount of L-lysine ethyl diisocyanate added is 3.02 g, the amount of 2-hydroxyethyl acrylate added is 1.51 g, and the final product is PEUA-3000.
[0104] Comparative Example 3
[0105] Comparative Example 3 completes steps S1 and S2 in Comparative Example 1, and its content is basically the same as that of Comparative Example 1, except that:
[0106] In step S1, PLCL-6000 obtained in step S1 of Example 3 is used;
[0107] In step S2, the amount of L-lysine ethyl diisocyanate added is 1.51 g, the amount of 2-hydroxyethyl acrylate added is 0.75 g, and the final product is PEUA-6000.
[0108] Comparative Example 4
[0109] Comparative Example 4 completes steps S1 and S2 in Comparative Example 1, and its contents are substantially the same as those in Comparative Example 1, except that:
[0110] In step S1, PLCL-8000 obtained in step S1 of Example 4 is used;
[0111] In step S2, the amount of L-lysine ethyl diisocyanate added is 1.13 g, the amount of 2-hydroxyethyl acrylate added is 0.58 g, and the final product is PEUA-8000.
[0112] The PEUA-PLCL prepared in Comparative Examples 1 to 4 was subjected to the above mechanical property test, and the mechanical properties were compared with those of the E-PLCL prepared in Examples 1 to 4. The results are shown in Table 2.
[0113] Table 2 Mechanical properties of E-PLCL and PEUA-PLCL
[0114]
[0115] It can be seen from Table 2 that by comparing E-PLCL with different molecular weights with PEUA-PLCL, E-PLCL has a lower elastic modulus, higher ultimate tensile stress and elongation at break, and better mechanical properties, indicating that the E-PLCL obtained by the present invention using terminal hydroxyl groups such as diols (or polyols) to react with allyl isocyanate to double-bond modify PLCL diol has higher mechanical properties than the polyurethane acrylate material modified by the traditional two-step method.
[0116] (III) Example of E-PLCL / DOX covered stent applied in the treatment of esophageal / tracheal cancer
[0117] Example 5
[0118] The content of Example 5 is basically the same as that of Example 1, except that: in step S3, 2% doxorubicin hydrochloride is added to the E-PLCL to finally obtain an E-PLCL / DOX coated stent, the appearance of which is shown in the following photo: Figure 8 a(i) is shown on the right and appears orange-red.
[0119] Example 5: An E-PLCL / DOX coated stent loaded with the thermosensitive chemotherapy drug doxorubicin (DOX) was prepared to provide mechanical support and local chemotherapy for trachea patients with tracheal cancer.
[0120] (1) Drug release behavior of E-PLCL / DOX coated stent
[0121] To study the drug release behavior of the E-PLCL / DOX coated stent, we immersed the E-PLCL / DOX film in 5 mL of PBS solution and placed it in a 37°C shaker to maintain a constant temperature. Every two days, 3 mL of PBS was taken out and the drug concentration was detected by UV spectrophotometer. At the same time, an equal amount of fresh PBS was added. The experiment lasted for 60 days. Fig.11 As shown in a, the cumulative release curve of DOX shows that the release of DOX in E-PLCL reaches 38% at 60 days. To further reveal the sustained release mechanism of DOX, we studied the relationship between drug release and E-PLCL coating degradation, and observed the surface morphology changes of the samples during drug release by SEM and EDS. The results are shown in Fig.11 b and 11c, where Fig.11 b shows the EDS analysis results, indicating that doxorubicin hydrochloride is evenly distributed in the system. Fig.11The SEM image of c shows that on the first day, crystalline DOX is evenly distributed on the surface of the E-PLCL coating, indicating that the initial release is mainly driven by the dissolution and diffusion process. After 30 days, the surface of the E-PLCL coating gradually degraded, exposing the DOX crystals embedded deeper in the coating, thereby promoting sustained drug release. By the 60th day, the E-PLCL coating had undergone significant erosion, allowing the DOX in the deep layer of the coating to be released. These results indicate that the drug release behavior of the E-PLCL / DOX coated stent is controlled by a dual mechanism: initially, DOX is released from the surface of the coating by dissolution and diffusion; as the E-PLCL coating gradually degrades, the DOX crystals embedded in the deep layer are gradually exposed and released, thereby achieving sustained release. The dual mechanism of dissolution-diffusion combined with material degradation ensures the controllability and continuity of drug release.
[0122] (2) Anticancer effect of E-PLCL / DOX coated stent
[0123] The anticancer effect of E-PLCL / DOX coated stent was evaluated by KYSE150 human esophageal squamous cell carcinoma cell activity assay, cell migration assay and apoptosis analysis ( Fig.12 First, E-PLCL / DOX films were prepared and incubated with tumor cells for 3 days. The CCK-8 method was used to detect the effects of different treatment groups on cell activity ( Fig.12 a). The results showed that the E-PLCL / DOX group significantly reduced the activity of tumor cells, and the difference was significant compared with the control group (Control, E-PLCL coated stent, no drug loading) and the E-PLCL group prepared in Example 1. At the same time, the inhibitory effect of different groups on the migration ability of tumor cells was studied by scratch test ( Fig.12 b), microscopic images showed that after 1 day (1D) and 3 days (3D) of culture, the degree of scratch closure in the E-PLCL / DOX group was the lowest, and the cell migration ability was significantly inhibited. However, the cell migration ability of the Control group and the E-PLCL group was strong, and the scratch closure was rapid. In addition, Annexin V-FITC / PI double staining flow cytometry analysis ( Fig.12 c) Apoptosis of KYSE150 tumor cells cultured for 3 days. The results showed that the E-PLCL / DOX group induced the highest rate of tumor cell apoptosis, especially a significant increase in late apoptosis, and the apoptosis effect was more significant compared with the Control group and the E-PLCL group. The above research results demonstrate the significant effect of the E-PLCL / DOX coated stent in inhibiting tumor cell proliferation, migration and promoting apoptosis, providing an efficient and controllable solution for the local treatment of tracheal tumors.
Claims
1. A coating material for a metal stent, characterized in that: The invention is composed of E-PLCL, a free radical inhibitor and a photoinitiator, wherein the addition amount of the free radical inhibitor is 0.05% to 0.5% of the weight of the E-PLCL, and the addition amount of the photoinitiator is 0.2% to 2% of the weight of the E-PLCL; the E-PLCL is prepared by double-bond modification of PLCL diol by allyl isocyanate.
2. The coating material for a metal stent according to claim 1, characterized in that: The free radical inhibitor is 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical or 2,2,6,6-tetramethylpiperidin oxide; the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or 2,4,6-trimethylbenzoyl ethyl phosphonate.
3. The coating material for a metal stent according to claim 1, characterized in that: The double bond modification method of the E-PLCL is as follows: PLCL diol is dissolved in toluene to form a solution with a concentration of 15wt% to 40wt%, and then allyl isocyanate is added, and the mixture is reacted at 50 to 80°C for 0.5 to 1.5h to obtain the obtained product; the molar ratio of the terminal hydroxyl group of the PLCL diol to allyl isocyanate is 1:(1.2 to 1.5).
4. The coating material for a metal stent according to any one of claims 1 to 3, characterized in that: The molecular weight of PLCL diol is 3,000 to 10,000.
5. The method for preparing the coating material for metal stent according to claim 1 or 2, characterized in that: The following steps are involved: Step S1: preparing PLCL diol; Step S2: dissolving PLCL diol in toluene to form a solution with a concentration of 15 wt% to 40 wt%, then adding allyl isocyanate, and reacting at 50 to 80° C. for 0.5 to 1.5 h to obtain E-PLCL; Step S3: E-PLCL is mixed with a free radical inhibitor and a photoinitiator, and bubbles are removed by ultrasound to obtain a coating material for a metal stent.
6. The method for preparing a coating material for a metal stent according to claim 5, characterized in that: Step S1: The specific method for preparing PLCL diol is as follows: lactide, ε-caprolactone, diol, and stannous octoate are added into a reaction kettle, and stirred for reaction at 130-160° C. under vacuum and oxygen-free conditions for 8-16 hours to obtain poly(L-lactide-co-ε-caprolactone) diol, i.e., PLCL diol; The molar ratio of lactide, ε-caprolactone and diol is 0.165:0.658:(0.01-0.0125); The diol is selected from one or more of 1,6-hexanediol, ethylene glycol or triethylene glycol.
7. A coated stent, comprising a metal stent and a coating layer, wherein the coating layer is formed by impregnating or coating the metal stent with the coating material for the metal stent according to claim 1 or 2, followed by photocuring.
8. The stent graft according to claim 7, characterized in that: The coated stent is also loaded with drugs, which are mixed into the coating material for the metal stent and loaded after being photocured together with the coating material.
9. The method for preparing a stent graft according to claim 7, characterized in that: The following steps are involved: (1) Immersing the metal stent in the metal stent coating material and ultrasonically treating at 40 to 50° C. for 25 to 35 minutes; (2) taking out the metal stent treated in step (1), and subjecting it to vacuum heat treatment at 40 to 50° C. for 15 to 25 minutes; (3) Curing the metal stent treated in step (2) under a 365-406 nm ultraviolet lamp for 10-15 min to obtain an E-PLCL fully coated stent.
10. The method for preparing a stent graft according to claim 9, characterized in that: The material of the metal bracket is nickel-titanium alloy or magnesium alloy.
Citation Information
Patent Citations
Aqueous polyurethane acrylate resin, and preparation and use thereof
CN101475679A
Anti-tumor intraluminal stent coating and preparation method application thereof
CN108653828A
Degradable outer stent and preparation method and application of stent
CN111760190A
Coated intraluminal stents and reduction of restenosis using same
US20030077312A1
Spiral coated stent with controllable gradient degradation, preparation method thereof and application thereof
US20210128795A1